Effects of Positive End-Expiratory Pressure on Lung Recruitment, Respiratory Mechanics, and Intracranial Pressure in Mechanically Ventilated Brain-Injured Patients - Robba, Chiara; Ball, Lorenzo; Nogas, Stefano; Battaglini, Denise; Messina, Antonio; Brunetti, Iole; Minetti, Giuseppe; Castellan, Lucio; Rocco, Patricia R. M.; Pelosi, Paolo (Frontiers in Physiology, 2021)
Background: The pathophysiological effects of positive end-expiratory pressure (PEEP) on respiratory mechanics, lung recruitment, and intracranial pressure (ICP) in acute brain-injured patients have not been completely elucidated. The primary aim of this study was to assess the effects of PEEP augmentation on respiratory mechanics, quantitative computed lung tomography (qCT) findings, and its relationship with ICP modifications. Secondary aims included the assessment of the correlations between different factors (respiratory mechanics and qCT features) with the changes of ICP and how these factors at baseline may predict ICP response after greater PEEP levels. Methods: A prospective, observational study included mechanically ventilated patients with acute brain injury requiring invasive ICP and who underwent two-PEEP levels lung CT scan. Respiratory system compliance (Crs), arterial partial pressure of carbon dioxide (PaCO2), mean arterial pressure (MAP), data from qCT and ICP were obtained at PEEP 5 and 15 cmH2O. Results: Sixteen examinations (double PEEP lung CT and neuromonitoring) in 15 patients were analyzed. The median age of the patients was 54 years (interquartile range, IQR = 39–65) and 53% were men. The median Glasgow Coma Scale (GCS) at intensive care unit (ICU) admission was 8 (IQR = 3–12). Median alveolar recruitment was 2.5% of total lung weight (−1.5 to 4.7). PEEP from 5 to 15 cmH2O increased ICP [median values from 14.0 (11.2–17.5) to 23.5 (19.5–26.8) mmHg, p < 0.001, respectively]. The amount of recruited lung tissue on CT was inversely correlated with the change (Δ) in ICP (rho = −0.78; p = 0.0006). Additionally, ΔCrs (rho = −0.77, p = 0.008), ΔPaCO2 (rho = 0.81, p = 0.0003), and ΔMAP (rho = −0.64, p = 0.009) were correlated with ΔICP. Baseline Crs was not predictive of ICP response to PEEP. Conclusions: The main factors associated with increased ICP after PEEP augmentation included reduced Crs, lower MAP and lung recruitment, and increased PaCO2, but none of these factors was able to predict, at baseline, ICP response to PEEP. To assess the potential benefits of increased PEEP in patients with acute brain injury, hemodynamic status, respiratory mechanics, and lung morphology should be taken into account.